REGIONAL DEVELOPMENT PLANNING IN THE EDUCATION SECTOR THROUGH SPECIAL AUTONOMY FUNDS (DOK) (Study of the Development Planning Cycle in Yahukimo Regency, Papua Mountain Province) - Nakamnanu, Kusi Hendra; Sumartono, S; Rochmah, Siti (Erudio Journal of Educational Innovation, 2024)
The aim of this research is to carry out an in-depth description and analysis of regional development planning in the field of education through the Special Autonomy Fund in the Yahukimo Regency. Apart from that, this research also aims to identify and analyze factors that can support or hinder regional development planning in the field of education through the Special Autonomy Fund in Yahukimo Regency, which will become recommendations for improving the quality of regional development planning in Yahukimo Regency.The type of research used is qualitative descriptive research. Data sources were taken using purposive sampling techniques, which are data collection techniques through observation, interviews, and documentation. The data analysis technique in the form of an interactive data analysis model from Miles Huberman (2014) consists of data collection, data presentation, data condensation, data conclusion drawing, data presentation, and conclusion drawing. The theory in this research uses 10 Regional Development Planning cycles, according to Sjafrizal (2016 ), which consists of assessing the current situation (existing conditions), assessing future development directions, formulating development goals and targets, reviewing alternative development strategies, setting development priorities, formulating development policies, identifying programs and activities, determining estimates of investment funds needed, setting indicators. Performance and Preparation of Action Plans. Meanwhile, in determining supporting and inhibiting factors, Rivaldi and Bratakusumah's (2004) theory is used, which consists of environmental factors (social and cultural), HR planning factors, system factors, science and technology development factors, and funding factors.The research results show that regional development planning in Yahukimo Regency, especially in the field of education through the Special Autonomy Fund, is still not optimal. Policy changes that occur must be analyzed relevantly and synergized between planning documents to answer the needs of Indigenous Papuans (OAP) and the future development direction of the Yahukimo Regency. Still not realistic, the preparation of alternative development strategies is still not appropriate between the Regional Long Term Development Plan (RPJMD) document and the Strategic Plan document (RENSTRA) of the Education Service, determining targets and priorities based on three main problems, namely low access to education, quality and competitiveness of education and education governance implemented through the Smart Yahukimo program, development policies implemented based on the principle of affirmative action for indigenous Papuans, programs and activities implemented through Smart Yahukimo but hampered by the dynamics of policy changes that occur, funding with a new pattern based on ten good impact variables, performance indicators has not been maximized due to limited data availability, the action plan cycle has been described in the Papua Development Acceleration Action Plan (RAPPP) for a five year period in general, but the monitoring and evaluation process is still not optimal. The supporting factors in this research are good HR planning factors so that they are able to complete the planning process on time, very high funding factors that exceed the minimum standards set, and system factors related to good Special Autonomy Fund Governance. Inhibiting factors in the planning process are environmental conditions with limited access and problems due to existing social and cultural values , as well as scientific and technological development factors that are not supported by good data and infrastructure.